fbl-Typing of Staphylococcus lugdunensis: A Frontline Tool for Epidemiological Studies, but Not Predictive of Fibrinogen Binding Ability - Dahyot, Sandrine; Lebeurre, Jérémie; Laumay, Floriane; Argemi, Xavier; Dubos, Charline; Lemée, Ludovic; Prévost, Gilles; François, Patrice; Pestel-Caron, Martine (Frontiers in Microbiology, 2019)
Staphylococcus lugdunensis is increasingly recognized as a potent pathogen, responsible for severe infections with an outcome resembling that of Staphylococcus aureus. Here, we developed and evaluated a tool for S. lugdunensis typing, using DNA sequence analysis of the repeat-encoding region (R-domain) in the gene encoding the fibrinogen-binding protein Fbl (fbl-typing). We typed 240 S. lugdunensis isolates from various clinical and geographical origins. The length of the R-domain ranged from 9 to 52 repeats. fbl-typing identified 54 unique 18-bp repeat sequences and 92 distinct fbl-types. The discriminatory power of fbl-typing was higher than that of multilocus sequence typing (MLST) and equivalent to that of tandem repeat sequence typing. fbl-types could assign isolates to MLST clonal complexes with excellent predictive power. The ability to promote adherence to immobilized human fibrinogen was evaluated for 55 isolates chosen to reflect the genetic diversity of the fbl gene. We observed no direct correlation between fibrinogen binding ability and fbl-types. However, the lowest percentage of fibrinogen binding was observed for isolates carrying a 5’-end frameshift mutation of the fbl gene and for those harboring fewer than 43 repeats in the R-domain. qRT-PCR assays for some isolates revealed no correlation between fbl gene expression and fibrinogen binding capacity. In conclusion, this study shows that fbl-typing is a useful tool in S. lugdunensis epidemiology, especially because it is an easy, cost-effective, rapid and portable method (http://fbl-typing.univ-rouen.fr/). The impact of fbl polymorphism on the structure of the protein, its expression on the cell surface and in virulence remains to be determined.